Differences in Bacterial Types in Controlled and Uncontrolled Type II Diabetes Mellitus with Urinary Tract Infections - Sakti, Hari Saktiningsih; Vector Stephen Dewangga; Sulasmi, Sulasmi (Jurnal Biologi Tropis, 2024)
Diabetes Mellitus (DM) is a group of metabolic disorders caused by various environmental, genetic and lifestyle factors as a result of a decrease in insulin secretion. An increase in the incidence of DM will certainly be followed by an increase in the possibility of chronic complications of DM. High glucose concentrations in urine are a good medium for the growth of pathogenic microorganisms, as a result, DM patients often experience urinary tract infections (UTI). The aim of this research is to find out the description of the identification of bacteria that cause urinary tract infections in controlled and uncontrolled type II diabetes mellitus. This research method uses an observational analytical research type with a cross-sectional approach. Data were analyzed descriptively to determine the identification of bacteria in controlled and uncontrolled DM.  The results of the research showed diabetes type 2 was uncontrolled with different types of bacteria, namely: Streptococcus sp (8.3%), Staphylococcus epidemidis (16.75), Salmonella paratyphi A (8.3%), Serratia marcescens (8.3% ), Pseudomonas aeruginosa (8.3%), Escherichia coli (16.67%), Enterococcus faecalis (8.3%), while controlled DM type 2 was found Staphylococcus aureus (8.3%), Escherichia coli (16.67%), Klebsiella pneumoniae (8.3%), Staphylococcus epidermidis (8.3%).